Lueur Tee's - Eizzuan, Ameer; Josely, Ann Sharoniza; Ali Rahman, Mohd Azizul (2017)
Our business plan will be focusing on T-shirt Printing services where our customer. This type of services is one of the most demanded services in the market such as students in Universities as well as public. The concept of this services is that customer may have their own printed design on their shirts that they wanted and it create the looks of unity among the students together with the society. In marketing our product, we focus on selling our services locally to increase the number of our customer around the area of Kota Kinabalu, Sabah. For the past few months we have sold quite numbers of shirts based on their own requests where the price is depends on the type of materials of the shirts, the quantity requests and the type of design printed which is heat press, silk screen, or embroidery. Therefore, we provide such services for die purpose of helping students in providing them a place to have the shirts that they desired. For an example, students prefer in having their own Faculty's shirt to represent themselves. Our management team which consists of three members and based on our agreement that we delegate evenly the tasks of doing the financial, marketing, and sales production.